Christian America in Black and White: Racial Identity, Religious-National Group Boundaries, and Explanations for Racial Inequality. (8th December 2018) - Perry, Samuel L; Whitehead, Andrew L
Abstract: Recent research suggests that, for white Americans, conflating national and religious group identities is strongly associated with racism, xenophobia, and Islamophobia, prompting some to argue that claims about Christianity being central to American identity are essentially about reinforcing white supremacy. Prior work has not considered, however, whether such beliefs may influence the racial views of nonwhite Americans differently from white Americans. Drawing on a representative sample of black and white Americans from the 2014 General Social Survey, and focusing on explanations for racial inequality as the outcome, we show that, contrary to white Americans, black Americans who view being a Christian as essential to being an American are actually more likely to attribute black–white inequality to structural issues and less to blacks' individual shortcomings. Our findings suggest that, for black Americans, connecting being American to being Christian does not necessarily bolster white supremacy, but may instead evoke and sustain ideals of racial justice.